Individual Perceived Stress Mediates Psychological Distress in Medical Workers During COVID-19 Epidemic Outbreak in Wuhan - Zhang C (Dove Medical Press, 2020)
Chen Zhang,1– 3 Daihui Peng,1– 3 Lu Lv,4 Kaiming Zhuo,1,3 Kai Yu,5 Tian Shen,4 Yifeng Xu,1,2 Zhen Wang1– 3 1Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Shanghai Key Laboratory of Psychotic Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Shanghai Psychological Medical Team Supporting Hubei, Shanghai, People’s Republic of China; 4School of Public Health, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 5MoE Key Laboratory of Artificial Intelligence, AI Institute Shanghai Jiao Tong University, Shanghai, People’s Republic of ChinaCorrespondence: Zhen Wang Email wangzhen@smhc.org.cnYifeng Xu Email xuyifeng@smhc.org.cnBackground: Since the novel coronavirus disease (COVID-19) outbreak in Wuhan, thousands of medical workers have been dispatched to support Wuhan against the virus. The purpose of this study was to identify the independent risk factors for psychological distress in order to develop a more effective strategy and precise evidence-based psychological intervention for medical workers.Methods: This multisite cross-sectional survey recruited doctors and nurses from local and nonlocal medical teams working at 16 hospitals in Wuhan to complete this online survey from February to March, 2020. Psychological status was evaluated through Perceived Stress Scales (PSS), Patient Health Questionnaire-9 (PHQ-9), General Anxiety Disorder Scale (GAD-7) and Acute Stress Disorder Scale (ASDS).Results: Of 966 participants, the prevalence of stress (95.9%), depression (46.0%) and anxiety (39.3%) were high. Local medical workers exhibited even higher scores of PSS, PHQ-9, GAD-7 and ASDS than those from outside Hubei (P< 0.001). Females had more severe perceived stress, depression and anxiety than males (P< 0.001). Multiple logistic regression showed that perceived stress is associated with increased odds of depression (OR=1.413; 95% CI: 1.338– 1.493; P< 0.001) and anxiety (OR=1.515; 95% CI: 1.407– 1.631; P< 0.001).Conclusion: Our findings demonstrated a high prevalence of stress, depression, anxiety and acute distress among medical workers on the front-line during the COVID-19 outbreak in Wuhan. The level of psychological impact may be mediated by individual perceptions of stressful events.Keywords: COVID-19, stress, anxiety, depression, Wuhan